2018
DOI: 10.29312/remexca.v9i5.1513
|View full text |Cite
|
Sign up to set email alerts
|

V238AC: nueva variedad de maíz de grano amarillo QPM

Abstract: Pocos productores de maíz pueden adquirir semilla certificada de híbridos, por lo que la otra opción para agricultores de escasos recursos es adquirir semilla certificada de variedades de polinización libre. En Chiapas se liberó la variedad V-534 en 1990 y fue muy apreciada por los productores llegándose a sembrar hasta 50 000 ha en su primer año con semilla certificada. En el año 2000 se inició un esquema de selección combinada de familias de hermanos completos en la V-534 con o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Cross 1217 showed acceptable yield and stability, as well as high starch (≥ 85 g 100 g -1 of dm) and oil (6.3 g 100 g -1 of dm) content, which are attributes that can improve the rheological characteristics of tortillas made with this grain, according to Vázquez-Carillo et al (2014). Although cross 1812 was found to have acceptable yield, stability and starch content, and ranked among the crosses named as outstanding for protein concentration (9.0 g 100 g -1 of ms), its protein content was considered to be in the normal range of variation, in agreement with the values reported by Vázquez-Carrillo et al (2014) and Vázquez-Carrillo et al (2018). In general, it was observed that the higher the protein content, the lower the starch concentration.…”
Section: Biochemical Nutritional Content Of the Grainsupporting
confidence: 86%
See 4 more Smart Citations
“…Cross 1217 showed acceptable yield and stability, as well as high starch (≥ 85 g 100 g -1 of dm) and oil (6.3 g 100 g -1 of dm) content, which are attributes that can improve the rheological characteristics of tortillas made with this grain, according to Vázquez-Carillo et al (2014). Although cross 1812 was found to have acceptable yield, stability and starch content, and ranked among the crosses named as outstanding for protein concentration (9.0 g 100 g -1 of ms), its protein content was considered to be in the normal range of variation, in agreement with the values reported by Vázquez-Carrillo et al (2014) and Vázquez-Carrillo et al (2018). In general, it was observed that the higher the protein content, the lower the starch concentration.…”
Section: Biochemical Nutritional Content Of the Grainsupporting
confidence: 86%
“…The starch concentration found in the crosses ranged from 72.6 to 96.6 g 100 g -1 of dm (Table 3); these values were higher than the ranges defined for previously studied maize (Arendt and Zannini, 2013), with different origin and level of improvement (Vázquez-Carrillo et al, 2018;Vázquez-Carrillo et al, 2014;Agama-Acevedo et al, 2011). Crosses 1214Crosses , 1417Crosses , 1418Crosses , 1713Crosses , 1714Crosses , and 1813 had more than 92 g 100 g -1 of dm and were rated as outstanding in this trait.…”
Section: Biochemical Nutritional Content Of the Grainmentioning
confidence: 57%
See 3 more Smart Citations